ELECTRICAL CONDUCTIVITY APPLICATION IN OHMIC PASTEURIZATION OF ORANGE JUICE - Hawri Ahmed; Arkan Sedeeq; Thamer Alhaji (Mesopotamia Journal of Agriculture, 2022)
The conversion of electrical energy into heat energy, which results in internal energy generation, is the underlying premise of Ohmic heating. An experimental batch Ohmic heating unit was built and manufactured for this study. The effect of voltage gradient of alternating current during batch Ohmic heating on orange juice was investigated. Parameters such as temperature, electrical current, time consumption, system performance coefficient, and heating rate of orange juice under Ohmic heating process were studied. The time consumption such as (23.02, 11.25, and 2.19 minutes) to reach the Ohmic pasteurization temperature (95 °C) was decreased as the voltage gradients (9.20 V/cm, 12.64 V/cm, and 25.28 V/cm) increased respectively. The electrical current was rapidly increased (4.46 Amp.) in accordance with the higher voltage gradient (25.28 V/cm) to attain the pasteurization temperature. With rising voltage gradients, Ohmic heating resulted in greater system performance coefficient values. The heating rate appears to have grown dramatically as the voltage gradients increased.